Problemas relacionados ao uso de medicamentos em pacientes coinfectados com tuberculose e HIV/AIDS - Natalia Helena de Resende (2017)
Human immunodeficiency virus infection represents a major challenge for the control of tuberculosis worldwide. The simultaneous treatment of the two infections, with effect of therapeutic ineffectiveness, adverse reactions, drug interactions and possibility of not good adherence to the treatment. Given this context, a multiprofessional approach counting on the pharmaceutical product in this team is very important for these patients, to identify and solve Drug Therapy Problems. The aim of this study was to describe, classify and quantify Drug Therapy Problems and as potential drug interactions in patients with tuberculosis and HIV / aids. A Cross sectional study was carried out in a referral hospital in infectious disease in Belo Horizonte. Drug Therapy Problem classification method was Pharmacotherapy Workup and the variables were investigated using a semi-structured questionnaire. Potential drug interactions were identified using Drug-Reax software. The categorical variables association analysis was performed using the chi-square or Fisher test. The Spearman coefficient was calculated to determine the correlation between the number of associated diseases, drugs and interactions. The logistic regression model was used to identify factors associated with the presence of Drug Therapy Problems. During the study period, 140 patients coinfected in the hospital were identified, 81 of them were included. Of the 81 interviewed, 65/81 patients had Drug Therapy Problems. A total of 110 Drug Therapy Problems were identified. 56/110 were related to the need for additional therapy and 39/110 for nonadherence to antiretroviral treatment. Patients were exposed to potential drug interactions 77/81, mainly severe and moderate. The most frequent interactions were between antituberculosis and antiretroviral drugs with potential to cause therapeutic ineffectiveness and adverse reactions. Excessive polypharmacy, such as associated diseases, the use of antiretroviral therapy, and the fact that patients were hospitalized had significant associations as interactions. The most frequent were related to indication and adherence to pharmacotherapy. The frequency of potential drug interactions during treatment was a high positive correlation between the number of drugs and associated diseases. As drug interactions, there is potential to induce therapeutic failures and serious adverse reactions such as hepatotoxicity and elevation of the QT interval.